Acclimatization of Pencil Orchid (Papillionanthe hookeriana Rehb.f) as Affected by Different Types of Planting Media and Fertilizing Frequency - Febriyani, Sustri; Ganefianti, Dwi W; Romeida, Atra; Herawati, Reny (Badan Penerbitan Fakultas Pertanian (BPFP), Fakultas Pertanian, Universitas Bengkkulu, 2019)
Acclimatization is a process of an environmental adaptation from heterotrophic conditions to autotrophic conditions. In order to be successful in acclimatization, it requires proper planting media and enough nutrition supply. The objective of this experiment were to determine the best planting media and the best spraying frequency of leaf fertilizer on Pencil orchid growth during acclimatization period. The experimental design used was Randomized Complete Block Design, arranged in factorial (2 factors, 3 replications). The first factor was type of planting media: Coconut Coil, Rockwool, Wood Shavings, and Fern Roots. The second factor tested was fertilizing frequencies: every 2 days, every 3 days, and every 4 days. The results showed that the best media for acclimatization of Pencil orchid was fern root fertilized every four days, the best media for growing Pencil orchid was fern root and Wood Shavings, and the best fertilizing frequency to promote Pencil orchid growth were every 3 days or every 4 days.Keywords: Pencil orchid, acclimatization, planting media, fertilization